Foreword: The Salmond Centennial 2006 - McLay, Geoff; Dorsett, Shaunnagh (Victoria University of Wellington Law Review, 2008)
This foreword introduces the articles published in this issue, presented at a symposium held at the Victoria University of Wellington Law School to celebrate the centennial of John Salmond’s arrival as the first fulltime in Law at the Victoria University College (as it was then called). The articles celebrate John Salmond’s intellectual contribution as a legal theorist and writer of textbooks, as chief law draughtsman and then Solicitor General, and as a Supreme Court judge.